Dampak Perubahan Penggunaan Lahan Terhadap Aliran Permukaan, Aliran Bawah Permukaan Dan Aliran Dasar Di Das Batugajah Kota Ambon - Ruddi Soplanit; Charles Silahooy (Faculty of Agriculture, Pattimura University, 2012)
The study was conducted to quantify the land use changes that have occurred in the watershed Batugajah and evaluate the impact of changes in land use to changes in surface flow, inter flow and base flow. The results showed that the change in land use in the watershed Batugajah of the year 1998-2010 as follows: The decline occurred from 215.70 ha forest area to forest area 58.88 ha or 28.73% decrease, increasing the wide use of residential land of 25 ha to 183.62 ha, an increase of 29.06%; vast improvement hamlet of 155, 65 ha to 221.78 ha, an increase of 12.12%. The impact of land use changes as follows: Runoff increased from 2288.35 mm to 2291.35 mm; annual runoff increased from 2525.81 mm to 2646.70 mm; interflo) increased from 103.382 mm to 244.99 mm; Water yield increased from 210.48 mm to 220.56 mm and the base flow dropped 141.07 mm to 110.35 mm.